2021
DOI: 10.1111/famp.12644
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Respiratory Sinus Arrhythmia in Romantic Relationships

Abstract: Respiratory sinus arrhythmia (RSA), an index of the parasympathetic nervous system, has recently gained attention as a physiological component of regulatory processes, social connectedness, and health. Within the context of romantic relationships, studies have operationalized and conceptualized RSA in disparate ways, obscuring a clear pattern of findings. This systematic review synthesizes the rapidly developing literature and clarifies the role of RSA in romantic relationships. We evaluate support for three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
5
0
1
Order By: Relevance
“…Jocelyn and Tag's RSA values, in contrast, demonstrate what we call a “tug‐of‐war” linkage pattern of time offset synchrony within which one individual's physiological arousal changed and the other followed with a similar arousal or de‐arousal pattern (see Figure 2). Jocelyn and Tag here seem to demonstrate a pattern of lagged synchrony, which has not been correlated specifically to either positive or negative relational quality (Han et al., 2021). In contrast to their low relationship satisfaction scores, however, Jocelyn and Tag's linked RSA values do demonstrate a distinct pattern of anti‐phase coordination, which generally has been associated with positive relational quality (ibid.).…”
Section: Case Studies: Physiological Linkages In Interactionmentioning
confidence: 83%
See 2 more Smart Citations
“…Jocelyn and Tag's RSA values, in contrast, demonstrate what we call a “tug‐of‐war” linkage pattern of time offset synchrony within which one individual's physiological arousal changed and the other followed with a similar arousal or de‐arousal pattern (see Figure 2). Jocelyn and Tag here seem to demonstrate a pattern of lagged synchrony, which has not been correlated specifically to either positive or negative relational quality (Han et al., 2021). In contrast to their low relationship satisfaction scores, however, Jocelyn and Tag's linked RSA values do demonstrate a distinct pattern of anti‐phase coordination, which generally has been associated with positive relational quality (ibid.).…”
Section: Case Studies: Physiological Linkages In Interactionmentioning
confidence: 83%
“…As described above, the current study focused specifically on investigating fluctuations in each partner's RSA, a reflection of activity in the parasympathetic arm of the autonomic nervous system (Cacioppo et al., 1994). RSA, in other words, is derived from HRV, but captures a component of the moment‐to‐moment regulation of arousal that serves as a particularly useful index of availability for affiliation and social intimacy (Cacioppo et al., 1994; Cribbit, 2013; DeCaro, 2016; Gates et al., 2015; Han et al., 2021; Porges, 2011).…”
Section: Methods and Analytic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Resting vagal tone (as measured by RSA) showed a negative association (d = −0.16, p = 0.20, k = 21), while vagal tone as measured by RMSSD (root mean square of successive differences) during task performance indicated a positive relationship, indicating increased vagal tone being associated with increased antisocial behavior (d = 0.36, p = 0.331, k = 18; de Looff et al, 2022), with increased vagal tone additionally being argued to be the most reliable autonomic correlate of psychopathy. Similarly, a systematic review of violence in romantic relationships concluded that high vagal tone was associated with increased relationship violence (Han, Baucom, Timmons, & Margolin, 2021). Overall, the main conclusion drawn from the extant literature to date is that findings on vagal tone and antisocial behavior are mixed (Glenn & McCauley, 2019;Zhang & Gao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…156 -172. noviembre 2023 www.alfapublicaciones.com permanente y controlar el ritmo o de la selección de dispositivos después de la ablación del nódulo aurículo ventricular Price C (2016). La arritmia sinusal respiratoria ayudara a los pacientes a brindar una regulación emocional en personas que tienen trastorno por consumo de sustancias, es una medida importante de los mecanismos subyacentes para los estudios de tratamiento del trastorno por consumo de sustancias, variación de la frecuencia cardíaca, control vagal, control vagal cardíaco, psicofisiológica, intervención, tratamiento, mente-cuerpo, salud mental, dependencia química y regulación emocional Han C et al (2021).…”
Section: Introductionunclassified